Practical handbook of remote sensing - Lavender, Samantha; Lavender, Andrew (CRC Press, 2023)
The number of Earth observation satellites launched in recent years is growing exponentially, along with the datasets they gather from free-to-access and commercial providers. The second edition of Practical Handbook of Remote Sensing is updated with a new chapter, new explanations and practical examples using the Copernicus satellite data and new versions of the open-source software. Thoroughly revised, and intended for those with no prior knowledge of remote sensing, the handbook continues to be a practical "how-to" guide. Professionals in administration, urban planning, environmental management, and students of geography and geosciences, will find this book helpful"--